Towards a Celebration of 50 Years of European Union - Angelo, A H; Plachecki, Rebekah C (Victoria University of Wellington Law Review, 2007)
The article provides an introduction to the articles found in this issue of the Victoria University of Wellington Law Review. The authors state that the purpose of the collection of articles is to mark and celebrate the creation of the European Union ('EU') while acting as clear evidence of the dynamism of the EU. The authors note that the articles reflect on a range of topics – many of them with direct relevance to the peoples and countries of the Pacific region.